Penerapan KUHP dalam Kasus Pemerkosaan dengan Korban Anak - Indraswati, Annisa (Program Studi Hukum Universitas Pamulang, 2025)
In today's era, when crime or criminal acts are problems experienced by humans from time to time, why crime can occur and how crime can be eliminated has always been a subject of debate. Crime is a problem that occurs because someone has lust but is not balanced with good common sense so that they dare to carry out actions beyond human thought, for example sexual crimes. Currently, sexual crimes are rampant in various forms. The perpetrators, in cases of rape, no longer recognize the status, rank, education, position, and age of the victim. All of this will be done after their lust is satisfied. Rape now occurs not only to adults but also to children. This study aims to determine the extent of the existing legal force to protect child rape victims. This study uses normative research, which reviews and evaluates issues related to books and laws. This study found that victims, regardless of age, have the same rights under the law.